Income Inequality Viewed from the Aspects of Welfare, Economy, and Demographics: Regression Analysis in the Cities of Malang, Madiun, and Surabaya - Ardhita Eko Ginanjar; Albrian Fiky Prakoso; Heny Musfidah; Komm Pechinthorn (International Journal of Emerging Research and Review, 2026)
Objective: This research seeks to identify the factors that potentially influence income inequality from the perspective of welfare (Human Development Index/HDI), economic factors (economic growth), and demographics (population) in the cities of Malang, Madiun, and Surabaya. Method: This study was conducted using a quantitative panel data regression method over the period 2020-2024, using Gretl software. Results: This study’s findings indicate that HDI has a positive and massive impact on income inequality. Economic growth has no significant effect, while population has a negative and big implication on income inequality. These results imply local government policies related to the equitable distribution of HDI, optimisation of economic growth, and the creation of job opportunities. Novelty: The novelty of this research lies in its focus on areas classified as cities by the central statistics agency in East Java, which face issues of income inequality, specifically the cities of Malang, Madiun, and Surabaya which have never been studied based on the most recent year.